Analisis Fungsi Keuntungan Usahatani Padi Sawah di Kecamatan Tanah Sepenggal Kabupaten Bungo - Situmorang, Agustinus; Nainggolan, Saidin; Damayanti, Yusma (Universitas Medan Area, 2026)
This study aims to analyze the profit function of rice farming in Tanah Sepenggal District, Bungo Regency. Specifically, this study (1) describes the characteristics of rice farming, (2) calculates the amount of profit earned by farmers, and (3) identifies the factors that influence the level of profit. The research employed a quantitative descriptive method approach using primary data collected from rice farmers through structured interviews in June- July 2025. Farm profit was calculated as the difference between total revenue and total cost, while the Cobb–Douglas profit function Unit Output Price (UOP) to examine the effect of seed cost, urea fertilizer cost, NPK fertilizer cost, pesticide cost, labor cost, and land rent. The results indicate that seed, pesticide, labor, and land rent costs significantly affect farm profit, whereas urea and NPK fertilizer costs do not. The coefficient of determination (R²) of 0.987 indicates that the model explains 98.7% of the variation in profit.